Implementasi Gaya Kepemimpinan Kontingensi dalam Pendidikan Islam di SD Taman Kalijaga Permai Cirebon - Aris Sabthazi; Fauziyah Hayati Fazrin; Agus Sutisna; Sarimah Sarimah; Yiyin Bayinah; Silmi Adha (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2024)
This article seeks to analyze and describe the application of contingency leadership style in the educational institution of Taman Kalijaga Permai State Elementary School, Cirebon City. This study uses qualitative research through case studies by conducting in-depth interviews on the leadership of the Principal of Taman Kalijaga Permai State Elementary School, Cirebon City, by making the basic concepts of contingency leadership style, namely tasks, relationships, organizational structure. The results of this study were able to provide an increase in positive relationships between leaders and those led, able to increase motivation within employees in the work environment, and able to manage orders with other employees effectively and efficiently. There is comfort, increased work motivation due to self-awareness that grows from interactions made by leaders to colleagues, subordinates in their organization. Flexible, willing to learn and adaptable nature provides changes in environmental dynamics. The conclusion of this research is that leadership by applying the principles of contingency leadership is able to face various situations and challenges in an organization. The leadership performed recognizes the importance of adaptability, situation recognition, staff involvement, and continuous leadership development. The implication is that leaders who support these principles will be more successful in leading their institutions or organizations effectively. However, in its application, it is not absolute that this contingency leadership style can be applied in all situations and circumstances, because abnormal circumstances will require the leader to adjust his attitude in making the right decision. In that situation the leader will use an authoritative or transactional style to solve the problem to match expectations. Styles other than contingency are not dominant only at certain times. This indicates that the dominant contingency leadership style compared to other leadership styles shows the successful management of the institution or organization. This shows adaptability and awareness of the circumstances that occur, is the key to successful leadership that continues to change.Keyword : Leadership Implementation; Contingency Leadership; Islamic Education